The Coming Collapse of China - Chang, Gordon G. (London Random House Business, 2001)
Beneath the veneer of modernization, the government of the People's Republic of China is corrupt and weak and - the author (a Chinese lawyer) predicts - has five, perhaps ten, years before it falls. Economic failure will be the trigger, and there is also the probability of a war with Taiwan.
Include Notes and Index
Keywords: China -- Politics and government -- Social conditions